Pembelajaran Berdiferensiasi Dengan Berbantuan Flipbook Untuk Meningkatkan Motivasi Belajar Anak - Sri Mujiatun; Arri Handayani; Dini Rakhmawati (Institut Nalanda, 2023)
Motivation to learn has an important role in the success of children in learning. With the motivation to learn, the learning process can be carried out optimally. This study aims to describe the implementation of flipbook-assisted differentiated learning to increase children's learning motivation. This type of research includes qualitative descriptive research. Differentiated learning aims to facilitate students to fulfill their learning needs. One effort that can be done by the teacher is to use flipbook learning media that can be adapted to the needs of children. The results of the study are to increase children's learning motivation, an appropriate strategy is needed, namely differentiation learning using flipbooks.